Untargeted metabolomics analysis of Ralstonia eutropha during plant oil cultivations reveals the presence of a fucose salvage pathway - Björn Gutschmann (Nature Portfolio, 2021)
Abstract Process engineering of biotechnological productions can benefit greatly from comprehensive analysis of microbial physiology and metabolism. Ralstonia eutropha (syn. Cupriavidus necator) is one of the best studied organisms for the synthesis of biodegradable polyhydroxyalkanoate (PHA). A comprehensive metabolomic study during bioreactor cultivations with the wild-type (H16) and an engineered (Re2058/pCB113) R. eutropha strain for short- and or medium-chain-length PHA synthesis has been carried out. PHA production from plant oil was triggered through nitrogen limitation. Sample quenching allowed to conserve the metabolic states of the cells for subsequent untargeted metabolomic analysis, which consisted of GC–MS and LC–MS analysis. Multivariate data analysis resulted in identification of significant changes in concentrations of oxidative stress-related metabolites and a subsequent accumulation of antioxidative compounds. Moreover, metabolites involved in the de novo synthesis of GDP-l-fucose as well as the fucose salvage pathway were identified. The related formation of fucose-containing exopolysaccharides potentially supports the emulsion-based growth of R. eutropha on plant oils.